Development of a Sensitive Outcome for Economical Drug Screening for Progressive Multiple Sclerosis Treatment - Kosa, Peter; Ghazali, Danish; Tanigawa, Makoto; Barbour, Chris; Cortese, Irene; Kelley, William; Snyder, Blake; Ohayon, Joan; Fenton, Kaylan; Lehky, Tanya; Wu, Tianxia; Greenwood, Mark; et al. (Frontiers in Neurology, 2016)
Therapeutic advance in progressive multiple sclerosis (MS) has been very slow. Based on the transformative role magnetic resonance imaging (MRI) contrast-enhancing lesions had on drug development for relapsing-remitting MS, we consider the lack of sensitive outcomes to be the greatest barrier for developing new treatments for progressive MS. The purpose of this study was to compare 58 prospectively-acquired candidate outcomes in the real-world situation of progressive MS trials, to select and validate the best-performing outcome. The one year pre-treatment period of adaptively-designed IPPoMS (ClinicalTrials.gov #NCT00950248) and RIVITaLISe (ClinicalTrials.gov #NCT01212094) Phase II trials served to determine the primary outcome for the subsequent blinded treatment phase by comparing eight clinical, one electrophysiological, one optical coherence tomography, seven MRI volumetric, nine quantitative T1 MRI, and 32 diffusion tensor imaging MRI outcomes. Fifteen outcomes demonstrated significant progression over one year (Δ) in the predetermined analysis and seven out of these were validated in two independent cohorts. Validated MRI outcomes had limited correlations with clinical scales, relatively poor signal-to-noise ratios (SNR) and recorded overlapping values between healthy subjects and MS patients with moderate-severe disability. Clinical measures correlated better, even though each reflects a somewhat different disability domain. Therefore, using machine-learning optimization, we developed a combinatorial weight-adjusted disability score (CombiWISE) that integrates four clinical scales: expanded disability status scale (EDSS), Scripps neurological rating scale, 25 foot walk and nine hole peg test. CombiWISE outperformed all clinical scales (Δ=9.10%; p=0.0003) and all MRI outcomes. CombiWISE recorded no overlapping values between healthy subjects and disabled MS patients, had high SNR and predicted changes in EDSS in a longitudinal assessment of 98 progressive MS patients and in a cross-sectional cohort of 303 untreated subjects. One point change in EDSS corresponds on average to 7.50 point change in CombiWISE with standard error of 0.10. A novel validated clinical outcome CombiWISE outperforms the current broadly utilized MRI brain atrophy outcome and more than doubles sensitivity in detecting clinical deterioration in progressive MS in comparison to the scale traditionally used for regulatory approval, EDSS.